Caribbean Cement Company Limited: Sports Club & Wellness Center Grand Opening under the distinguished patronage of the Most Hon. Andrew Holness, ON, MP, Prime / Minister - Caribbean Cement Company Limited (Carib Cement).
This programme was done for the grand opening of the Caribbean Cement Limited Sports Club and Wellness Center. The event was done under the patronage of the Most. Hon. Andrew Holness ON, MP Prime Minister and took place on Thursday, September 8, 2016. The event started at 6:00 P.M with cocktails and at 7:50 PM. Entertainment and dinner with fab5 began.
Keywords: Caribbean Cement Company Limited (Carib Cement) -- Programme -- Jamaica